Negotiating Sundanese Cultural Values through Family WhatsApp Communication: Intergenerational Identity Work in Sundanese WhatsApp Groups - Wahyudin Aep; Supratman Lucy Pujasari; Sarbini Ahmad; Solahudin Dindin (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines how Sundanese cultural values are negotiated and communicated through family WhatsApp group interactions in everyday digital communication. The research aims to explore how family members reproduce cultural meanings and maintain relational values through routine online interaction. The study contributes to communication studies by providing insight into the role of digital family communication in shaping cultural identity within the context of Indonesian local culture. A qualitative approach was employed using thematic analysis informed by semiotic interpretation. Data were collected from three Sundanese family WhatsApp groups in West Java, Indonesia, over a three-month observation period. The data consists of text-based conversations containing greetings, advice, religious expressions, humor, and everyday family discussions. The findings show that Sundanese cultural values are communicated through recurring interactional patterns such as politeness, respect toward elders, expressions of care, humility, and religious discourse. These interactions demonstrate that WhatsApp group communication functions not only as a medium for information exchange but also as a space where cultural meanings are continuously negotiated through everyday interaction. The study highlights the importance of digital family communication in sustaining social relationships and cultural identity within contemporary mediated environments.